Efeitos do ácido elágico sobre a reatividade vascular em artérias de resistentes de ratas hipertensas e ovariectomizadas - Silva, Fabricio Braganca da (2019)
The postmenopausal period is considered a milestone for the emergence of chronic noncommunicable diseases, including cardiovascular diseases. In this context hypertension and endothelial dysfunction form the basis of the main risk factors and injuries. The introduction of nutraceuticals as therapeutic alternatives has attracted the attention of researchers for presenting promising results. These include ellagic acid, a phytochemical with potent antioxidant properties found in fruits, plants, and nuts. Therefore, the objective of this research was to evaluate the effects of ellagic acid treatment on vascular reactivity of resistance arteries in an experimental model of hypertension and menopause. Therefore 40 SHR rats were evaluated for 4 weeks and separated into 5 groups according to treatment: vehicle-treated SHAM (carboxymethylcellulose); OVX, castrated and vehicle treated; OAE, castrated and treated with ellagic acid (10 mg / kg / day); OE2, castrated and treated with estrogen (1g / kg / day); OAE + E2, treated with ellagic acid and estrogen. Mesenteric artery rings were maintained in vitro and subjected to contraction strength tests in the absence and presence of the nitric oxide synthase enzyme inhibitor to record the effect of treatments and the participation of nitric oxide (NO). Vessel samples were taken for biochemical analysis. Castration produced an increase in blood pressure (MAP: 190.4 ± 4.4 mmHg); effect that did not occur in groups treated with ellagic acid (MAP: 165.7 ± 1.4 mmHg, p